Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada Toko Inti Sari Palembang - Aras Tulip; Tutik Pebrianti; Indah Mawarni; Imam Suroso; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
This study aims to determine whether there is an influence of leadership style on employee performance at Toko Inti Sari Palembang. The sample in this study was 19 respondents of Toko Inti Sari Palembang, data obtained from the distribution of questionnaires. The technique used in this sampling is to use the Profortionate Stratified Random Sampling technique. The analysis method used is quantitative and uses the product moment correlation formula and the coefficient of determination.The results of this study show that the leadership style variable (X) has a rcalculated (0.489) > rtable (0.468) meaning that there is a positive and significant influence between the leadership style variable (X) on employee performance (Y), then H0 is rejected and Ha is accepted, meaning that leadership style has a positive and significant effect on employee performance at Toko Inti Sari Palembang. The value of the coefficient of determination was 0.239 or 23.9%, the leadership style variable could affect employee performance variables, while the remaining 76.1% was influenced by other factors not discussed in the study.